(untitled) (Raparin Journal of Humanities (RJH), 2020)
Following the demise of the Shah regime, Saddam Hussein capitalized on the deteriorating situation of Iran to attack the country in a bid to achieve a set of goals. He never thought that the war would last eight years. Before Iraq kicked off the conflict, Saddam and other Iraqi leaders had apparently gathered with American officials in Jordan. It is highly likely that Saddam declared war on Iran with the consent of the USA, though both sides categorically have rejected such accusations. Saddam seized the fallout of Iran-US relations to introduce himself as the guard protecting America’s interests. Even if the US was not responsible for the ignition of the war, it liked it as Iran at the time had American hostages behind its bars, a crisis which emerged in November 1979. In the meantime, the new Iran emerged to portrait itself as a major foe of the US. Though Jimmy Carter chose neutrality amidst the conflict, it asked for an immediate pause. The equation, however, turned up side down soon after Washington started to assist Iraq. One indication is that, two months before the war started, Baghdad and the US had decided to normalize ties, but announcing it was delayed as the war had been looming in order to avoid miscalculations from other sides. Through the war, the US wanted to destroy the infrastructure of both sides in order to cripple them from emerging as two powerful regional states. Through third parties, Washington was selling arms to both sides. The US had even warned Iran of Iraq’s military attack plan. The age of Carter’s age came to an end shortly after the war began when he lost the elections to Ronald Reagan and that a new administration took office in January 1981.